New families of Unlike degree Wiener Index (UDWI)for Graph Structures - Dr. S.S. Sandhya ,Sarasree.S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this work we introduced a novel concept concept Unlike degree Wiener index (UDWI) for some graph structures .We study the unlike degree Wiener Index for few graph structures such as Caterpillar,